Atypical Carcinoid Neuroendocrine Tumor of the Ureter: A Case Report and Literature Review - Yuen, Huay Shan; Rix, Gerald Henner; Sen, Soumadri; Kusuma, Venkata Ramana Murthy (The Surgery Journal, 2018)
Neuroendocrine tumors (NETs) of the ureter are rare, with less than 40 cases described in the literature. A majority of tumors described are poorly differentiated tumors with a poor prognosis. We present the case of a moderately differentiated atypical carcinoid NET of the ureter with a good postoperative outcome. A literature review was also performed to identify similar cases to compare their management and postoperative outcomes.
Keywords: atypical; carcinoid; neuroendocrine tumor; ureter